Bio-based multilayer films: A review of the principal methods of production and challenges - La Fuente Arias, Carla Ivonne; Kubo, Mirian Tiaki Kaneiwa [UNESP]; Tadini, Carmen Cecilia; Augusto, Pedro Esteves Duarte (Taylor & Francis, 2021)
The development of biodegradable packaging materials has been drawing attention worldwide to minimize the environmental impact of traditional petroleum-based plastics. Nevertheless, it is challenging to obtain bio-based materials with suitable properties for packaging applications. Films produced from a single biopolymer often lack some important properties. An alternative to overcome this limitation is the multilayer assembly. Under this technology, two or more materials with specific and complementary properties are combined into a single-layered structure, thus improving the performance of bio-polymer plastics. This review presents the main aspects of bio-based multilayer film production technologies, discussing their advantages and disadvantages, which have to be considered to produce the most suitable film for each specific application. Most of the studies reported that such films resulted in increased mechanical performance and decreased water, oxygen, and dioxide carbon permeability. This approach allows the addition of compounds leading to antioxidant or antibacterial activity. Finally, a discussion about the future challenges is also presented.
Keywords: Biodegradable; biopolymers; casting; electrospinning; extrusion; Layer-by-Layer deposition; molding; packaging; plastic